Nutrient Status and Mycorrhizal Population on Various Food Crops Grown Following Corn Inoculated with Indigenous Mycorrhiza on Sandy Soil of North Lombok, Indonesia (JOURNAL OF TROPICAL SOILS, 2016)
This study was aimed to determine the nutrient status and population of arbuscular mycorrhizal fungi (AMF) on the second cropping cycle of corn-based cropping patterns which utilized indigenous mycorrhizal fungi on sandy soil. The experiment was conducted at the Akar-Akar village in Bayan district of North Lombok, in a Randomized Block Design, with 4 replications and 6 treatments of cropping cycles (P0 = corn-soybean as a control, in which the corn plants were not inoculated with AMF; P1 = corn-soybean, P2 = corn-peanut, P3 = corn-upland rice, P4 = corn-sorghum, and P5 = corn-corn, in which the first cycle corn plants were inoculated with AMF). Results indicated that the status of N, P, K and organic-C increased significantly up to 112%, 148%, 88%, 88% at 60 DAS and 66%, 135%, 54%, 60% at 100 DAS, respectively in the second cropping cycle of sorghum compared to control. Uptake of N, P, K and Ca the sorghum plants at 60 DAS of the second cropping cycle reached 200%; 550%; 120% and 490%,  respectively a higher than in the control. Mycorrhizal populations (spore number and infection percentage) were highest in the second cycle sorghum, achieving 335% and 226% respectively, which were significantly higher than those in the control.
Keywords: Arbuscular mycorrhizal fungi; corn; cropping pattern; dryland; NPK